The impact of audit paradigm and obedience pressure on perceived audit judgment - Dina Heriyati, H. Habiburrochman, Widi Hidayat, (Opción, 2020)
This study aims to describe and critically examine and compare the influence of audit paradigm and obedience pressure on perceived audit judgment between novice and experienced auditors via questionnaires distributed to two groups which consist of accounting students that already took auditing course and internal auditors from several public universities in east java, Indonesia. The empirical results find that there is a significant difference in perceived audit judgment between novice and experienced auditors. In conclusion, ethics education should be a long term learning process throughout an auditor’s professional life to promote appropriate fairness or moral judgments.